Combating Energy Poverty in the Social Housing Stock - Lis, P.; Mazurkiewicz, J. (Економічний вісник Донбасу, 2015)
The authors of this publication indicate that in the second decade of the 21st century European Union institutions have been aiming at encompassing social housing construction into a common climate and energy policy. It has been shown that the justification of public support for energy investments in the social housing stock is an attempt to counteract climate changes, reduce energy poverty among low-income households as well as to promote local workplaces and economic development in a given area. The cohesion policy of the European Union may actively contribute to strengthening its dynamics and ensure a leverage effect which in turn will lead to the use of other, additional sources of finance. In accordance with the guidelines of the European Commission, the housing stock has been qualified to be subject to support from structural funds in the new financial perspective until 2020, especially in terms of thermomodernisation and promotion of renewable sources of energy, integrated actions aiming at developing urban areas and combating exclusion by providing access to dwellings to marginalised communities and offering high quality, affordable social services. Автори цієї публікації вказують, що в другому десятилітті XXI століття інститути ЄС націлені на енергетичну політику в побуті і її вплив на загальний клімат. Показана виправданість громадської підтримки інвестицій в економію енергії в побуті як спроба нейтралізувати зміни клімату, скоротити бідність серед сімей з низьким рівнем доходу і, щоб просувати місцеві робочі місця і економічний розвиток в цій області. Єдина політика Євросоюзу активно сприяє зміцненню його динаміки і гарантує ефект важеля, який у свою чергу призводитиме до використання інших, додаткових джерел фінансування. Відповідно до директив Єврокомісії, житлова сфера була кваліфікована, як така що підлягає підтримці від структурних фондів в новій фінансовій перспективі до 2020 р., особливо в термінах термомодернізації і просування поновлюваних джерел енергії. Але він доки не об'єднав дії, що націлюють розвиток міст на боротьбу за економію енергоресурсів, забезпечення доступу до житла маргіналізованим суспільствам і пропозицію соціальних послуг високої якості. Авторы этой публикации указывают, что во втором десятилетии XXI столетия институты ЕС нацелены на энергетическую политику в быту и ее влияние на общий климат. Показана оправданность общественной поддержки инвестиций в экономию энергии в быту как попытка нейтрализовать изменения климата, сократить бедность среди семей с низким уровнем дохода и, чтобы продвигать местные рабочие места и экономическое развитие в данной области. Единая политика Евросоюза активно содействует укреплению его динамики и гарантирует эффект рычага, который будет в свою очередь приводить к использованию других, дополнительных источников финансирования. В соответствии с директивами Еврокомиссии, жилищная сфера была квалифицирована, как подлежащая поддержке от структурных фондов в новой финансовой перспективе до 2020 г., особенно в терминах термомодернизации и продвижения возобновляемых источников энергии. Но он пока не объединил действия, нацеливающие развитие городов на борьбу за экономию энергоресурсов, обеспечение доступа к жилью маргинализированным обществам и предложение социальных услуг высокого качества.